Pengaruh Pembelajaran Pengantar Acara Agama Hindu Kaharingan Terhadap Keterampilan Membuat Sarana Upacara Keagamaan Mahasiswa Prodi Pendidikan Agama Hindu IAHN TP Palangka Raya - Rima Noktayani; Pranata Pranata; I Gede Dharman Gunawan (Institut Agama Hindu Negeri Tampung Penyang Palangkaraya, 2024)
This research is based on the problems that the author found in the Hindu religious education study program for the 2023/2024 academic year. Research found that students' skills, especially in making ceremonial facilities, can be said to be lacking. This can be seen from the fact that there are still many students who have not been able to make ceremonial facilities such as making ketupat, tawar containers, decorations in the lap for basarah, lack of interest in making ceremonial facilities, and there are still students who are not focused on the learning process so that in this case it requires more efforts to improve student skills in making ceremonial facilities. The purpose of this study is to find out whether there is an influence of learning the introduction of Hindu religious events on the skills of making religious ceremony facilities for students of the Hindu religious education study program of the Hindu Religious Institute of the State Tampung Penyang (IAHN TP) Palangka Raya. This type of research uses a quantitative research approach, with survey methods and data collection methods used for observation, documentation, and questionnaires. Learning data was obtained from distributing questionnaires/questionnaires by distributing them to respondents whose number was already known, namely 52 respondents, while skill data was obtained from the final semester exam scores (UAS) of students in grades A and B in the even semester of the 2023/2024 academic year, the data was analyzed by simple regression using IBM Statistics for windows. From the results of the research that has been carried out, the hypothesis in this study indicates that t count (0.017) < t table (1.675), it can be concluded that the results of the research and discussion in this study do not have an influence between the learning of the introduction of Hindu religious events in Kaharingan and the skills in making ceremonial facilities for students of the Hindu religious education study program class A and class B in the even semester of the 2023/2024 academic year and with a learning period In the high category there were 13 people with a percentage of 6.9%, in the medium category there were 37 with a percentage of 19.47% and in the low category there were 2 people with a percentage of 1.6% of the total 52 respondents.